Editorial - Blaufox, M. D. (Current Medical Imaging, 2006)
Two observations emerge from a review of the articles contained in this issue of CMIR. The first and perhaps most important is the remarkable growth in diagnostic technology. PET imaging has increased in utilization during the past several years so that it is now a part of the state-of-the-art of cancer care. The increased availability of combined PET/CT imaging has greatly fostered its growth and increased the specificity and accuracy of the technology. During the same time interval, faster and faster multi slice computed tomography devices have become available so that at the present time a 16 slice CT machine is pretty much the state-of-the-art, with 32 slice machines moving into the clinical area and 64 slice machines not far behind. The ultimate cardiac approach on the horizon appears to be the combination of a 64 slice CT with a PET machine so that patients would be able to have non-invasive coronary angiography performed at the same sitting with physiologic studies demonstrating perfusion and leading to decisions regarding cardiac intervention with no need for a cardiac cath. Of course, as this technology becomes more and more refined, there is an unavoidable increase in the cost of medical diagnosis. We have yet to learn the balance between physical examination, imaging technology and patient care. Unfortunately too many physicians move quickly to diagnostic studies without a careful intervening medical history and physical examination. That said, the other observation is that in this issue, which contains 13 articles, 8 are directly related to studies of the brain. It is remarkable that although a remarkable amount of work has been directed towards the study of the brain utilizing CT, MRI, and PET, the roles of these modalities in clinical medicine do not reflect volume of physiologic research. MR and CT have certainly become standard techniques for evaluating the brain but as demonstrated in these articles much of the information derived is still in the research sphere. Even more impressive is the general lack of utilization of PET in studies of brain disease while it has played a profound role in defining diseases such as Alzheimer's disease, multi infarct dementia, and other serious brain afflictions. It is evident from a review of these articles that diagnostic technology is improving at a logarithmic rate. It is also evident from the large number of research publications in the various areas that the movement from the laboratory to clinical medicine continues to lag. We are faced with an explosive growth in diagnostic methodology during the next decade. How this will impact on financing of medical care and on the algorithms for diagnosis of disease is something that will be a painful evolution both politically and economically based with a revolution medically and scientifically.